2012
DOI: 10.2478/s11534-012-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of BDD thin film electrode for electrochemical decomposition of heterogeneous aromatic compounds

Abstract: Abstract:The aim of the presented study is to investigate the applicability of electrochemical oxidation of aromatic compounds containing heteroatoms, e.g. waste from production of pesticides or pharmaceutics, at a borondoped diamond (BDD) electrode. The BDD electrodes were synthesized by microwave plasma enhanced chemical vapour deposition (MW PE CVD). Investigation of the electrode surface by optical microscopy and scanning electron microscopy (SEM) confirmed that the synthesized layer was continuous and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Using this type of electrode results in almost complete mineralization of waste during electrolysis, where carbon dioxide is the primary final degradation product. 161 Coupling light irradiation or ultrasound to anodic oxidation further improves the results attained by anodic oxidation alone. This improvement results from the increase in the formation of hydroxyl radicals and mass transfer.…”
Section: Anodic Oxidation and Cathodic Dechlorinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this type of electrode results in almost complete mineralization of waste during electrolysis, where carbon dioxide is the primary final degradation product. 161 Coupling light irradiation or ultrasound to anodic oxidation further improves the results attained by anodic oxidation alone. This improvement results from the increase in the formation of hydroxyl radicals and mass transfer.…”
Section: Anodic Oxidation and Cathodic Dechlorinationmentioning
confidence: 99%
“…Thus, the oxidation assessments of bupiramate, chlorpyrifos, chloroxylenol, mecoprop, methamidophos, parathion, propham, and mixtures of pesticides have confirmed that electrochemical oxidation with conductive diamond electrodes can be used to successfully treat pesticides with much higher current efficiencies than other anodic oxidation technologies. Using this type of electrode results in almost complete mineralization of waste during electrolysis, where carbon dioxide is the primary final degradation product …”
Section: Use Of Electrochemical Technologies For Pesticide Removal Fr...mentioning
confidence: 99%
“…57 However, although increases in current density can reduce the time required to oxidize the pollutant electrochemically, it also reduces the electrode current efficiency. 58 According to the result reported by D. Montanaro and E. Petrucci, 48 the discolouration of 50 mg L À1 of RBBR on BDD electrode at 30 mA cm À2 was observed aer 260 min. Hence it is clearly from the above results, the removal rate of RBBR on 5CBD electrode was faster than that on BDD electrode.…”
Section: Electro-degradation Of Rbbrmentioning
confidence: 79%
“…Previous studies on the treatment of mixtures are reported using contaminants with similar chemical properties . However, in terms of degradation, the key difference between pollutants is based on their aromatic or aliphatic structure . Hence, when a comparison is to be done, it is good to select two very different models of pollutants to be oxidized.…”
Section: Introductionmentioning
confidence: 99%